Simulation of Monsoon Precipitation over South-Asia Using RegCM3. (4th January 2012) - Basit, Abdul; Raza, S. Shoaib; Irfan, N.; Avila, R.
Abstract : The objective of this study is to explore the capability of the Regional Climate Model (RegCM3), to predict the extreme weather events in south-Asian region with particular reference to precipitation during monsoon season (July, August and September) over northern mountainous and southern plain regions of Pakistan. Different cumulus parameterization schemes in RegCM3 for prediction of convective precipitation are tested for monsoon period during the years 1998 and 2001. The model results are compared with the Climate Research Unit (CRU) observational data and the surface synoptic data of the Pakistan Meteorological Department (PMD). The year 1998 was a dry year and proved to be the beginning of a severe drought lasted up to the year 2000. While in year 2001 the precipitation over some parts of the country exceeded the normal, especially the northern parts of the country observed exceptionally high rainfall rate. The results indicate that some convective parameterization schemes of RegCM3 well captured the summer monsoon precipitation over Pakistan. However, the schemes need to be selected carefully depending upon the region of interest. It was found that the Grell scheme with both closures: Arakawa-Schubert (AS) and Fritsch-Chappell (FC) satisfactorily captured the monsoon phenomenon in Pakistan specially for the northern mountainous regions.